Plasmodium Parasitaemia and Urine Alterations among Pregnant Women Attending Antenatal Care in Aba Metropolis, Abia State, Nigeria - Paula Melariri; Chioma Ihemanma; Udoka Chigbo; Kirstie Eastwood; Chika Uche; Paschal Etusim (Journal of Parasitology Research)
Malaria presents a huge threat to pregnant women, their foetus, and children below five years. This study is aimed at assessing malaria prevalence, associated clinical symptoms, and urine abnormalities among pregnant women in Aba metropolis, Abia State, Nigeria. A cross-sectional study involving 450 pregnant women purposively selected from nine health care centres was conducted. Data were analysed using SPSS version 26. The overall malaria prevalence rate was 68.4% (n=308). Age group of 21-25 years had the highest prevalence rate of 20.4% (n=92) while the least was recorded among the age group of 41-45 years (17 (3.8%)). Pregnant women in their first trimester had the greatest prevalence rate of 28.6% (n=129), and the least prevalence was recorded among those in their third trimester (7 (15.6%)). The primigravidae were mostly infected at the rate of 27.7% (n=125) whereas the multigravidae recorded the least prevalence of 85 (18.9%). Participants with secondary education were the most susceptible at the rate of 38.6% (n=174). The infected participants exhibited significantly higher frequencies of reported fever (p>0.001, OR 12.881, 95% CI 3.977-41.725) and headaches (p<0.001, OR 4.688, 95% CI 1.819-12.083). However, cold, cough, body pains, poor appetite, and catarrh showed no significant association with malaria infection at p>0.05. Participants using long-lasting insecticidal nets (LLINs) showed significantly lower prevalence rate of malaria infection (p<0.001, OR 2.485, 95% CI 1.619-3.814). Malaria-infected participants showed statistically significant frequencies of proteinuria (p<0.001, OR 274.14, 95% CI 16.91-4444.0), bilirubinuria (p<0.001, OR 49.29, 95% CI 11.01-186.34), and urobilinogenuria (p<0.001, OR 65.16, 95% CI 4.00-1062.40) than those not infected. Ascorbic acid, nitrate, and ketone showed no significant associations with malaria infection at p>0.005. Infected participants had statistically significant amber and clear urine colour whereas there was no statistically significant difference between the pH levels of urine of the malaria-infected and malaria-noninfected pregnant women.